2017
DOI: 10.1038/s41598-017-03492-4
|View full text |Cite
|
Sign up to set email alerts
|

Intravascular forward-looking ultrasound transducers for microbubble-mediated sonothrombolysis

Abstract: Effective removal or dissolution of large blood clots remains a challenge in clinical treatment of acute thrombo-occlusive diseases. Here we report the development of an intravascular microbubble-mediated sonothrombolysis device for improving thrombolytic rate and thus minimizing the required dose of thrombolytic drugs. We hypothesize that a sub-megahertz, forward-looking ultrasound transducer with an integrated microbubble injection tube is more advantageous for efficient thrombolysis by enhancing cavitation-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
50
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 71 publications
(53 citation statements)
references
References 54 publications
(58 reference statements)
0
50
0
Order By: Relevance
“…Ultrasonic energy may be delivered to infected areas either extracorporeally or using catheter-based ultrasound probes. Catheters have been reported previously for sonothrombolysis (Owens 2008;Kim et al 2017), and could be investigated for sonobactericide in vascular organs.…”
Section: Clinical Translation Of Sonobactericidementioning
confidence: 99%
“…Ultrasonic energy may be delivered to infected areas either extracorporeally or using catheter-based ultrasound probes. Catheters have been reported previously for sonothrombolysis (Owens 2008;Kim et al 2017), and could be investigated for sonobactericide in vascular organs.…”
Section: Clinical Translation Of Sonobactericidementioning
confidence: 99%
“…One study again uses the EKOS system, which is a side-viewing low power, high frequency transducer, and demonstrates that this device is able to improve clot lysis outcomes with tPA and microbubble mediated sonothrombolysis in an in vitro deep vein thrombosis model [115]. Another study from our research group developed a forward viewing, sub-megahertz intravascular transducer for sonothrombolysis treatment which aims to be applied for deep vein thrombosis [116]. These parameters were optimized for microbubble mediated sonothrombolysis without the need for a thrombolytic agent, and in vitro studies have shown great success in treating blood clots with this technique.…”
Section: Intravascular Sonothrombolysismentioning
confidence: 99%
“…Thus, it was important to evaluate the feasibility of miniaturizing the FFMD to human-compatible dimensions. The catheter-based design is also intended for integration onto a catheter that emits therapeutic levels of ultrasound energy via either a forward-looking 44 or radially-emitting ultrasound transducer 45 and contains on-chip sensors for real-time monitoring and control of microbubble production rate and diameter. 46 The present study focused on ischemic stroke, but a multi-function sonothrombolysis catheter could find application in stroke, deep vein thrombosis, myocardial infarction, and other thrombosis-related conditions including those pertaining to the microvasculature.…”
Section: Miniaturization Of Ffmds To Human-compatible Dimensionsmentioning
confidence: 99%